PENGARUH PERSEPSI MEREK JASA TERHADAP SERVICE QUALITY, VALUE DAN LOYALITAS PELANGGAN: STUDI INDUSTRI LOW COST AIRLINES INDONESIA - Samuel Pandhega; Sri Rahayu Hijrah Hati; Savira Miranti (MIX: JURNAL ILMIAH MANAJEMEN, 2016)
Abstract. This paper investigate the effect of service brand on customer value andloyalty. Speciffically, the study examines the influence of brand image, companyimage, employee trust and company trust on service quality, customer value andloyalty. The data were collected from a total of 222 customers of 7 low cost airlines. AStructural Equation Modeling (SEM) is used to assess the relationships of the researchmodel. The result shows that it is brand image which has significant influence on bothservice quality and customer value while employee trust and cost has significantinfluences on customer value.